Vitamin D Deficiency in Axial Spondyloarthritis is Associated With Higher Disease Activity - Sizheng ZHAO,; Daniel THONG,; Stephen DUFFIELD,; Nicola GOODSON, (Archives of Rheumatology, 2017)
Objectives: This study aims to assess whether vitamin D deficiency is associated with increased disease activity and functional impairment in axial spondyloarthritis (axSpA), with control for its seasonal variation. Patients and methods: Serum 25-hydroxyvitamin D [25(OH)D] levels were measured in 235 consecutive axSpA patients (176 males, 59 females; mean age 46.3 years; range 18 to 85 years) attending a specialist spondyloarthritis service in the United Kingdom. Disease activity and functional status were assessed using Bath Ankylosing Spondylitis indices, C-reactive protein, and erythrocyte sedimentation rates. Vitamin D deficiency was defined as 25(OH)D <30 nmol/L. Associations between vitamin D deficiency and: (i) disease activity (Bath Ankylosing Spondylitis Disease Activity Index), (ii) spinal pain, (iii) functional impairment (Bath Ankylosing Spondylitis Functional Index), and (iv) inflammatory markers were explored using multivariable logistic regression models (adjusted for age, sex, vitamin D supplementation, and seasonal variation). Results: Median symptom duration was 17 years (inter-quartile range 8.5 to 28.6 years). Median 25(OH)D was 54.5 nmol/L (inter-quartile range 34 to 77 nmol/L) and 52 patients (22%) were deficient for vitamin D. Increasing Bath Ankylosing Spondylitis Disease Activity Index (adjusted odds ratio 1.23; 95% confidence interval 1.06-1.41), spinal pain visual analog scale (adjusted odds ratio 1.21; 95% confidence interval 1.07-1.38), and C-reactive protein (adjusted odds ratio 1.02; 95% confidence interval 1.01-1.04) were each significantly associated with 25(OH)D deficiency. Conclusion: This cross-sectional study demonstrated associations between vitamin D deficiency and both higher disease activity and functional impairment in axSpA. Whilst this may reflect reduced ultra-violet exposure in functionally impaired patients, it supports the hypothesis that vitamin D may have an immunomodulatory role. Interventional studies are needed to evaluate a potential causal relationship, as optimizing vitamin D may be a cost-effective adjunctive intervention to modify disease activity in axSpA.